Jogos de percussão corporal pela pedagogia da corporeidade para crianças do ensino fundamental - Sousa, Pryscilla Firmino Andrade de (2024)
This research objective was to analyze the effects of body percussion games on the perception of one's own rhythm in children in the 1st year of Elementary School. It’s a descriptive research with a qualitative approach. The research took place during Physical Education classes of students in the first year of Elementary School at a public school in Fortaleza (Ceará). Throughout twelve weeks (two weekly classes), twenty-four themed classes of fifty minutes each were applied, an intervention of 1,200 minutes. The classes were applied according the Corporeity Pedagogy Laboratory Class structure, that organizes the teaching-learning process as a path to knowledge experience, based on movement situations: Feeling, Reacting and Reflecting. Rhythmic games are categorized in the Pedagogy of Corporeity as being the secondary genre, endowed with types and styles. In this study, we used Touched and Body style games. We analyzed the rhythm construction (origin) in ultradian time (class time) and integrated into the environment (manifestation). Analyzing data, we used the pragmatic semiotic method of Corporeality Pedagogy, interpreting the effects of Emotional meaning, based on the Face Scale instrument (a scale that presents facial expressions). And the effects of Energy sense, through an observation script, based on filmed classes, from the sound of Intensity, Tempo and Pulse categories. The effect of Logical meaning was perceived through the children's drawings. The results indicated an increase in rhythmic perception in children and a positive correlation between satisfaction in classes and their performance in body percussion activities. Thus, we described how children recognize and experience the sound categories, relating them to their own body and the viability of the methodology applied in classes, attesting to the relevance of educational work towards body percussion.